Spit (smokeless) tobacco use by high school baseball athletes in California. (1st June 2000) - Walsh, Margaret M; Ellison, James; Hilton, Joan F; Chesney, Margaret; Ernster, Virginia L
Abstract : OBJECTIVE: To describe the prevalence, patterns, and correlates of spit (smokeless) tobacco (ST) use in a sample of high school baseball athletes in California. DESIGN: This cross sectional study was a survey of 1226 baseball athletes attending 39 California high schools that were randomly selected from a list of all publicly supported high schools with baseball teams. At a baseball team meeting, athletes who agreed to participate and had parental consent completed the study questionnaire. To enhance the accuracy of self reported ST use status, a saliva sample was collected from each subject. The questionnaires and saliva samples were coded and salivary cotinine assay was performed on a random subsample of 5% of non-users who also were non-smokers. Biochemical assay indicated that 2% tested positive for cotinine inconsistent with self reported ST non-use. RESULTS: Overall, 46% had ever used ST and 15% were current users. Odds ratios and 95% confidence intervals (CI) suggested that, among high school baseball athletes, age, living in a rural area, being white, smoking cigarettes, drinking alcohol, not knowing about the adverse effects of ST, perceiving little personal risk associated with ST use, and believing that friends, role models, teammates, and same age baseball athletes in general used ST, increased the likelihood of being an ST user. CONCLUSION: The findings indicate that considerable experimentation with ST products occurs among high school baseball athletes in California, and many are current users. ST interventions targeting this population are needed to stop the transition from experimental ST use to tobacco dependence. Correlates of ST use for consideration in future intervention studies are identified.